VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

VEQ’s Summer 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Breastfeeding Get Together - Jeffery Hale Community Services (2019)

Financial Statements - Voice of English-speaking Quebec (VEQ) (2019)

VEQ’s Spring 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Report to the Community : Highlights from 2018-2019 and Overview of Where We're Headed - Jeffery Hale - Saint Brigid's (JHSB) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)